Drawn together - d uthor; Santat, Dan (Los Angeles : Disney-Hyperion, 2018)
A boy and his grandfather cross a language and cultural barrier using their shared love of art, storytelling, and fantasy.
School Library Journal starred, June 2018
Bulletin of the Center for Children's Books starre, June 2018
Pub Weekly, March 2018
Kirkus Starred, May 2018
2.8
K-3
Keywords: Communication -- Juvenile fiction; Art -- Juvenile fiction; Storytelling -- Juvenile fiction; Grandfathers -- Juvenile fiction; Communication -- Fiction; Art -- Fiction; Storytelling -- Fiction; Grandfathers -- Fiction